2018
DOI: 10.1038/s41598-018-32801-8
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy protects the kidney from acute ischemic injury

Abstract: A complex analysis of acute kidney injury (AKI) in pregnant women shows that it is caused by the interaction of gestation-associated pathologies and beneficial signaling pathways activated by pregnancy. Studies report an increase in the regeneration of some organs during pregnancy. However, the kidney response to the injury during pregnancy has not been addressed. We investigated the mechanisms of the pregnancy influence on AKI. During pregnancy, the kidneys were shown to be more tolerant to AKI. Pregnant anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…We assessed the proliferative capacity of primary cultures of RTCs obtained from young and old kidneys by the real-time monitoring of the cell growth rate ( Figure 5 A). The analysis was performed by using iCELLigence, which has already been used for studying proliferation and the death of RTCs [ 32 ]. We found that RTCs isolated from the kidneys of young rats characterized by a more rapid growth rate exceeding the growth of old cells by more than 4 fold ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the proliferative capacity of primary cultures of RTCs obtained from young and old kidneys by the real-time monitoring of the cell growth rate ( Figure 5 A). The analysis was performed by using iCELLigence, which has already been used for studying proliferation and the death of RTCs [ 32 ]. We found that RTCs isolated from the kidneys of young rats characterized by a more rapid growth rate exceeding the growth of old cells by more than 4 fold ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of cells growth kinetics was performed using an RTCA iCELLigence™ instrument (ACEA, San Diego, CA, USA). This method is based on using electrical impedance of cell-covered electrodes [ 31 ] and may be used in particular for studies of RTCs proliferation and death [ 32 ]. The iCELLigence RTCA instrument was placed in a humidified incubator at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…There are very few actual models of pregnancy-related AKI. One exception is the model of AKI by Popkov et al in which pregnant rats underwent unilateral IR on gestational day 18 for 40 min [ 21 ]. The study of kidney injury during hypertensive pregnancies such as HELLP syndrome and preeclampsia is important for understanding the mechanisms involved in both the short- and long-term adverse consequences associated with these disorders [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NP+AKI rats as well as HELLP+AKI rats also had significant evidence of kidney damage (increased KIM-1, BUN, and creatinine, and decreased urine output) compared to NP rats, which was accompanied by decreased T regulatory cells and decreased sEng. While in the current study we only examined pregnant animal models, it should be mentioned that it has been suggested that the effects of IR on the kidney during pregnancy are less severe compared to what occurs in the non-pregnant state, suggesting that pregnancy increases the tolerance of the kidneys to AKI [ 21 ]. Examining AKI in non-pregnant rats is out of the scope of the current study; therefore, we cannot refute this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation